Proprioceptive Mechanism for Bioinspired Fish Swimming - Sánchez-Rodríguez, Jesús; Celestini, Franck; Raufaste, Christophe; Argentina, Médéric (American Physical Society, 2021)
In this Letter, we propose a mechanism for driving bioinspired fish swimming locomotion based on proprioceptive sensing. Proprioception provides information about and representation of a body’s position, motion, and acceleration in addition to the usual five senses. We hypothesize that a feedback loop based on this “sixth” sense results in an instability, driving the locomotion. In order to test our assumptions, we use a biomimetic robot and compare the experimental results to a simple yet generic model with excellent agreement.
https://openpolicyfinder.jisc.ac.uk/id/publication/13640
Keywords: Peces - Locomoción; Locomoción animal; Equilibrio (Fisiología); Flow-structure interactions; Locomotion; Swimming; Fish